The Impact of COVID-19 on Pilgrimages and Religious Tourism in Europe During the First Six Months of the Pandemic - Mróz, Franciszek (Journal of religion and health, 2021)
This study presents the results of the examination of the influence of the SARS-Cov-2 coronavirus pandemic on religious tourism and pilgrimages to selected Catholic pilgrimage sites in Europe during the first six months of the COVID-19 pandemic (March-September 2020). Field research conducted in shrines and on several pilgrimage routes involved interviews with shrine custodians and staff as well as pilgrims. Data regarding tourism and pilgrimage movement were also gathered. Research results have shown that the tourism and pilgrimage movement to the analysed shrines decreased by 90-95% during the first six months of the pandemic. The shrines in Santiago de Compostela and Lourdes were closed for a few weeks during the first wave of coronavirus spread. The influence of the pandemic on the age structure of pilgrims is noticeable, with a distinct decrease in the number of pilgrims aged 60 + . Also, the reasons for pilgrimages to shrines have changed. The overriding principle followed by shrine custodians and organisers of pilgrimages was to ensure the safety of pilgrims on their way to shrines and, most importantly, in the shrine areas. The largest Catholic shrines in Europe encouraged pilgrims to deepen their bonds with the shrine through participation in online services and prayers and to pursue spiritual and virtual pilgrimages. The study also shows a model of the development of pilgrimages and religious tourism during the COVID-19 pandemic.